A Study on the difficulties in English Speaking for EFL Students - Eva Meidi Kulsum; Acep Yaspi Jamjami; Aip Syaepul Uyun; Ayang Winda Sri Widianingsih (Journal on Education, 2025)
This research aims to identify the difficulties students experience in speaking English. A qualitative descriptive method was used to investigate these challenges by distributing questionnaires and conducting interview sessions. The study was conducted at a junior high school in Bandung, with eighth-grade students as the research participants. To gather valuable data, 26 students were selected using purposive sampling. The findings revealed that students face several difficulties in learning to speak English, including challenges with understanding grammar, fluency, pronunciation, limited vocabulary, lack of self-confidence, shyness, anxiety, and lack of motivation. Additionally, it is implied that by addressing the root causes of these difficulties, such as fear and lack of motivation, teachers can help enhance students' ability to communicate effectively in English.